1999
DOI: 10.1074/jbc.274.28.20017
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Reactive Oxygen Species in Serum-induced and Platelet-derived Growth Factor-induced Growth of Airway Smooth Muscle

Abstract: Reactive oxygen species have been recently identified as important mediators of mitogenic signaling in a number of cell types. We therefore explored their role in mediating mitogenesis of airway smooth muscle. The antioxidants catalase, N-acetylcysteine, and probucol significantly reduced proliferation in primary cultures of rat tracheal smooth muscle stimulated with fetal bovine serum or platelet-derived growth factor, without affecting cell viability or inducing apoptosis. N-Acetylcysteine also significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 66 publications
3
77
0
Order By: Relevance
“…The flavoproteincontaining enzyme inhibitor Diphenyleneiodonium (DPI) has been widely used to evaluate the activity of this pathway. DPI has been shown to inhibit Ang II, thrombin and PDGF mediated induction of ROS production in VSMC (31,34,35). When cells were pretreated with 10 µM DPI prior to stimulation with Ang II, HIF-1α induction was completely inhibited (Fig.…”
Section: Interestingly Recent Results Have Suggested a Possible Rolementioning
confidence: 87%
See 2 more Smart Citations
“…The flavoproteincontaining enzyme inhibitor Diphenyleneiodonium (DPI) has been widely used to evaluate the activity of this pathway. DPI has been shown to inhibit Ang II, thrombin and PDGF mediated induction of ROS production in VSMC (31,34,35). When cells were pretreated with 10 µM DPI prior to stimulation with Ang II, HIF-1α induction was completely inhibited (Fig.…”
Section: Interestingly Recent Results Have Suggested a Possible Rolementioning
confidence: 87%
“…Recent evidence has convincingly shown that in VSMC, Ang II, thrombin and PDGF can modulate the expression and activity of different elements of the NAD(P)H oxidase system (32)(33)(34)(35)(36). This system is responsible for strong increases in intracellular ROS levels found in these cells after growth factor and hormone stimulation.…”
Section: Reactive Oxygen Species Are Necessary For Ang II Induced Hifmentioning
confidence: 99%
See 1 more Smart Citation
“…Administering ROS activates a wide variety of proteins in various pathways; for example, platelet-derived growth factor (PDGF), EGF, mitogen-activated protein kinase (MAPK), protein kinase C (PKC) and protein kinase B (PKB/Akt) signal-transduction pathways. H 2 O 2 generation during the activation of PDGF, transforming growth factor and EGF receptor signaling has also been well established (Sundaresan et al, 1995;Bae et al, 1997;Brar et al, 1999;Junn et al, 2000;Okuyama et al, 2001). The H 2 O 2 generated results in tyrosine phosphorylation of the receptor, which subsequently activates MAPK (Gamou and Shimizu, 1995).…”
Section: Intracellular Redox State and Cell Cycle Proteinsmentioning
confidence: 95%
“…Nitric oxide can inhibit deoxyribonucleic acid (DNA) synthesis and the proliferation of airway smooth muscle. Reactive oxygen species generated by an oxidoreductase of reduced nicotinamide adenine dinucleotide are required for serum or PDGF-induced growth of airway smooth muscle cells [56]. Furthermore, superoxide dismutase mimetics are capable of inhibiting serum-induced proliferation of airway smooth muscle cells [55].…”
Section: Mediators Of Airway Smooth Muscle Proliferationmentioning
confidence: 99%